Gallbladder and biliary tract cancer burdens in China from 1990 to 2021 and projection to 2044: findings from the 2021 Global Burden of Disease study - Jiang, Zhongyi; Jiang, Qianwei; Wang, Pusen; Zhong, Lin (Frontiers in Medicine, 2025)
BackgroundGallbladder and biliary tract cancers (GBTCs) have high incidence and mortality rates in China, imposing a substantial disease burden. Establishing comprehensive strategies is crucial for alleviating this burden. We report the average estimated annual percentage change (EAPC) in age-standardized rates (ASRs) of GBTCs globally and in China via Global Burden of Disease (GBD) study 2021 data and the relationships of GBTCs with body mass index (BMI) and the sociodemographic index (SDI). The 2021–2044 GBTCs prevalence trends were predicted by sex.MethodsWe collected and analyzed GBD data from 1990 to 2021, including incidence, prevalence, deaths, disability-adjusted life years (DALYs), and age-standardized incidence (ASIR), prevalence (ASPR), mortality (ASMR), and DALYs (ASDR) rates and calculated the proportion of deaths and DALYs attributable to risk factors by sex. Future trends from 2022 to 2044 were predicted with Nordpred age–period–cohort models.ResultsThe number of GBTCs-related incident cases, prevalent cases, deaths, and DALYs increased from 1990 to 2021. However, the GBTCs-related ASMR and ASDR decreased during the same period. These changes may be related to risk factors, such as increased BMI. Furthermore, we used the projection model to estimate that the GBTCs-related ASPR in all populations will steadily increase, whereas the GBTCs-related ASMR and ASDR are expected to significantly decline until 2044.ConclusionThe increasing GBTCs prevalence in China due to SDI advancements and population aging underscores the importance of early monitoring and prevention measures to alleviate the disease burden.